Revitalizing Nepal's Carpet Industry: Strategic Location Planning and Supply Chain Optimization in Special Economic Zones - Khanal, Rishav; Labh, Shacheendra Kishor; Sanjog, J. (Himalayan Journal of Applied Science and Engineering, 2025)
The lack of proper planning, policies, omitting the domestic market and increased product value has caused drastic downfall of carpet industry in Nepal. Once being the major exported material from the nation, now is surviving solely because of USA, causing a drastic downfall over last decade in terms of quantity demanded. Demand forecasting establishes the declining trend. The major reason for the downfall is noted to be high cost which omits the chances of revival and survival in domestic market. To decrease the cost, the supply of raw materials must be considered through roadways from India and China, replacing expensive airways from  New-Zealand. To strengthen the findings, forecasting methods, including Moving Average, Weighted Moving Average, and Exponential Smoothing, were utilized to predict demand trends and assess their implications for strategic planning. The least value of RMSE was obtained for Exponential Smoothing, establishing its accuracy and reliability. The drastic increase in the population of Kathmandu has caused many industries to migrate, leading the Government to plan Special Economic Zones (SEZ) in various locations across Nepal. To meet demand, facilities have been strategically located, focusing on utilizing government-provided resources in SEZ to support the industrial expansion. Additionally, the Center of Gravity (CoG) method was employed using latitude and longitude coordinates in MATLAB, validated through conventional methods, to identify optimal facility locations. Sample calculations demonstrated the applicability of the CoG technique, with Simara and Bhairahawa emerging as favorable SEZs based on varying scenarios. Location planning techniques like Center of  Gravity (CoG) and cost modeling helped to identify the most optimal location for the expanding industries based upon the demand of the product across the nation, crucial for the anticipated growth of domestic carpet industries in the years to come.